A society acceptance towards rehabilitated drug addicts - Mohamad Noor, Norazleen; Che Hassan, Norlizah; Zain, Sarina (Fakultas Ilmu Tarbiyah dan Keguruan, UIN Syarif Hidayatullah Jakarta, 2017)
This study has been conducted at Rumah PENGASIH, Malaysia and Cure & Care Service Centre under Agensi Anti Dadah Kebangsaan. The purpose of this study is to see what makes them involves in drug. According to Pengasih President, Datuk Yunus Fathi, the residences that underwent rehab in PENGASIH started drugging habit while being at school. They also consistently skipped classes before starting their drugging behaviour. Moreover, the residences who underwent rehab in PENGASIH and Cure & Care Service Centre loves staying out late from home until wee hours of the morning before starting their drugging behavior. It is important for parents to communicate with schools to check on their children's attendance, require children to come home early before night fall and maintain some form of discipline. If parents are careless of these points, the risks are very high. Once children are on drugs, it will be a very painful journey to recovery for them and for the families. Recovering addict always seeks and sensing hopes to fully recover from their addictions. In order to sense the hope to recover, family support plays an important roles during this phase. Respondent had stated the statements that demonstrate the support received. Several studies have shown that support from family is importance to the drug addicts. Former addicts need supports from the family and surrounding for not returning to drugs. Without support, the former addicts might have the attention to relapse because of they have lower self-esteem and self-confident. Support is like the device in other to maintaining recovery among the former addict and support from significant person is needed.